Teaching Student Speaking Skill Through Media Audio -Visual With The Short Movie The king’s Speech At SMKN 1 Sepuluh - Iahah, Maslahah; Kiptiyah, Mariyatul (Asosiasi Ide Bahasa Kepri, 2024)
The purpose of this study is to describe students' experiences using movies as learning media and how the use of movies affects students' speaking skills. Teaching speaking is not just about teaching students to produce spoken words to express their feelings, such as ideas and thoughts but also to facilitate students in negotiating facilitate students in negotiating means using general knowledge of the situation and subject. This research is a descriptive qualitative research with purposive sampling technique of students at SMK N 1 . Data collection methods were carried out by observation and interview. Data analysis techniques using milles huberman. The results showed that short movie can be used as an alternative learning resource for teaching speech so that students are not bored. The high enthusiasm of students can make students more active and easy to understand. Additionally, short films like The King's Speech can provide students with a powerful example of the importance of effective communication in public speaking.This is modeled after King George VI. Students will learn about the challenges faced when speaking in public and how to overcome these obstacles with will and effort.By analyzing the techniques used in this film, such as breathing exercises and proper use of pauses, students will gain valuable insight into how to improve their speaking skills.This is not just academic learning, but also learning that inspires and motivates students to overcome their fears and develop self-confidence in public speaking.